A REVIEW: INFLUENCE OF NATURAL DAYLIGHTING ON QURANIC MEMORISATION (HAFAZAN) LEARNING TASK - Raja Nur Syaheeza, Raja Mohd Yazit; Elina, Mohd Husini (E-JOURNAL ON LANGUAGE PRACTICE & INFORMATION TECHNOLOGY, 2018)
In Islamic point of view and other monotheistic religion such as Christianity and Judaism, light has been described as a sacred element. Surah An-Nur in the Quran emphasised light as synonym to Allah’s guidance. Interpreted by Buya Hamka, the first word of the first revelation “READ!” shows that in order to understand Islam, one must read and learn from the Quran. In Quran memorization (hafazan), the most acceptable method is reciting/reading and rewriting the verses. These methods or learning tasks are influenced by the daylighting condition of the classroom. Researches shows that sufficient daylighting improves the students’ performance such as cognitive skills, mood, behaviour and alertness. Those are the reasons that daylight is important and need to be considered in educational spaces. This review paper includes literature review on the preferred learning task for hafazan and the effect of daylighting towards students’ performance. The paper also refers to the traditional ‘madrasah’ method of hafazan, which uses a ‘rehal’ as practiced since the tenth century by the Seljuq dynasty. The recommended daylight in standards and guidelines are measured at 900 mm table height or working plane from floor level. Human ergonomics shows that clearance height for a cross-legged task is minimum of 300 mm, similar to the height of a ‘rehal’. The difference of height between a modern table and a ‘rehal’ shows that the illuminance level measured will be different. In conclusion, further study should be established in order to identify the acceptable illuminance level at different working plane height.